A study on efficacy of employee training: review of literature - Vijayabanu, Chidambaram; Amudha, Ramachandran (Business: Theory and Practice, 2012)
The success of any organization depends on appropriate use of human assets available in the organization. All other assets could only be supplementary to human assets. Towards augmenting the human resources and to cope with changes – both internal and external, the organization has to concentrate necessarily on developing the ability, wisdom and skills of its workforce. For the development of human asset, ‘training’ becomes the base. Training is a tool to attain individual, organizational needs related to the jobs undertaken and is also intended to improve the work culture of the group involved in a group task. An ideal training programme can be expected to change the attitude, skills and develop forward vision of the participants towards the task. This paper summarizes the results of the literature review on the effectiveness of training programmes of employees from diverse perspective.